Windows presentation foundation unleashed - Nathan, Adam, 1977- (Unleashed., 2006)
Printed entirely in color, with helpful figures and syntax coloring to make code samples appear as they do in Visual Studio. Windows Presentation Foundation (WPF) is a key component of the .NET Framework 3.0, giving you the power to create richer and more compelling applications than you dreamed possible. Whether you want to develop traditional user interfaces or integrate 3D graphics, audio/video, animation, dynamic skinning, rich document support, speech recognition, or more, WPF enables you to do so in a seamless, resolution-independent manner. Windows Presentation Foundation Unleashed is the authoritative book that covers it all, in a practical and approachable fashion, authored by .NET guru and Microsoft developer Adam Nathan. · Covers everything you need to know about Extensible Application Markup Language (XAML) · Examines the WPF feature areas in incredible depth: controls, layout, resources, data binding, styling, graphics, animation, and more · Features a chapter on 3D graphics by Daniel Lehenbauer, lead developer responsible for WPF 3D · Delves into non-mainstream topics: speech, audio/video, documents, bitmap effects, and more · Shows how to create popular UI elements, such as features introduced in the 2007 Microsoft Office System: Galleries, ScreenTips, custom control layouts, and more · Demonstrates how to create sophisticated UI mechanisms, such as Visual Studio-like collapsible/dockable panes · Explains how to develop and deploy all types of applications, including navigation-based applications, applications hosted in a Web browser, and applications with great-looking non-rectangular windows · Explains how to create first-class custom controls for WPF · Demonstrates how to create hybrid WPF software that leverages Windows Forms, ActiveX, or other non-WPF technologies · Explains how to exploit new Windows Vista features in WPF applications.